Tahliil al'Ahaadiith al-Zaaifah fi Khitaab al-Wataniyyah wa' Akhlaaqiyyaat al-'Amal bi al-Fadha' al-Raqamy - Abdullah Ubaid; Nasrulloh Nasrulloh; Muh. Faruq; Al Lastu Nurul Fatim; Azzah Saniyyah (Sharia Faculty of Universitas Islam Negeri Maulana Malik Ibrahim Malang, Indonesia, 2026)
This study examines the role of Arabic as a form of symbolic authority in the construction of pseudo-religious authority through the dissemination of pseudo-hadith within narratives of nationalism and work ethics in digital spaces. The study employed a qualitative approach using Critical Discourse Analysis (CDA) combined with takhrij al-hadith methods. The data consisted of digital religious content containing Arabic quotations collected from Instagram, Facebook, TikTok, and YouTube. Data were analyzed through text identification, hadith verification, and discourse interpretation. The findings reveal that Arabic possesses strong symbolic capital due to its association with the Qur’an, hadith, and the Islamic scholarly tradition, enabling it to generate religious legitimacy for messages circulated in digital media. Pseudo-hadith are utilized as instruments of symbolic legitimation to reinforce narratives of religious nationalism and Islamic work ethics, despite lacking authentic hadith status. Furthermore, social media contributes to the reproduction of religious authority through digital popularity, algorithmic visibility, and symbolic representation. This study concludes that the acceptance of pseudo-hadith in digital spaces is shaped not only by textual validity but also by the symbolic power of Arabic and the logic of digital information distribution that constructs contemporary religious legitimacy.